Analisis PAD dan Dana Perimbangan Terhadap Kinerja Keuangan Pemda Se-Jawa Barat - PUSPITA_AYU, PUTRI (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2018)
The research is to find out and analyze the contribution of Original income Equalization Funds against the region and the financial performance of local Government Counties and the city of se-West Java province. Hypothesis testing in this study using multiple regression analysis (Multiple Regression) on the grounds that its independent variable more than one. This analysis is used to determine the relationship between financial performance areas with independent variables (the original Revenue Equalization Fund and regional). To know the influence between independent variables with the performance levels of local government then performed testing of hypothesis testing research on the variables with the determination coefficient and t-test. Linear regression analysis of the barganda equation KKPD = 1.452 + 0, 561PAD – 0, 171DP + e. Whereas determinasinya coefficients (R2) of 25.3%. based on the research results obtained the conclusion that Equalization Fund of PAD effect partially against the financial performance of local government.